Amlodipine Seems To Be Superior to Valsartan in Decreasing Microalbuminuria in Newly Diagnosed Hypertensive Patients: A Novel Effect To Be Explained with Hyperfiltration?. (April 2013) - Ay, Seyit Ahmet; Cakar, Mustafa; Karaman, Murat; Balta, Sevket; Demirkol, Sait; Unlu, Murat; Kurt, Omer; Altun, Battal; Akhan, Muharrem; Arslan, Erol; Koc, Bayram; Bulucu, Fatih
<x xml:space="preserve">Abstract</x> Background: Microalbuminuria (MA) is common in hypertensive population and is a marker for endothelial dysfunction and a predictor of increased cardiovascular risk. A great body of data shows the importance of MA as a strong predictor of renal and cardiovascular disease (CVD) risk in hypertensive population. Aim: In this study, we aimed to compare the anti-albuminuric effects of an angiotensin II receptor antagonist, valsartan, with a calcium channel blocker, amlodipine, in newly diagnosed hypertensive patients. Material and methods: Totally, 20 patients were recruited into the study. Patients were randomized to one of the following intervention protocols: An (a) angiotensin II receptor blocker (valsartan, 80–320 mg/day) or (b) calcium channel blocker (amlodipine, 5–10 mg/day), for 12 weeks immediately after baseline measurements. Ten patients were randomized into valsartan group and 10 patients into the amlodipine group. Twenty-four-hour urinary albumin excretion (UAE) levels of the patient groups were measured before treatment and on the 12th week. Results: Patients of the two groups were matched for age and body mass index. In the amlodipine group, baseline urine microalbumin levels were higher compared to valsartan group, although the difference was not statistically significant (p = 0.082). At the 12th week, there was a significant decrease in urine microalbumin levels in the amlodipine group, but no significant change was observed in the valsartan group. Conclusion: Amlodipine seems to be superior to valsartan in decreasing UAE. To reduce cardiovascular risks, endothelial dysfunction, and microinflammation, these factors are taken into consideration while prescribing antihypertensive drugs in hypertensive patients.